A miniaturized electronic sensor for instant monitoring of ethanol in gasohol fuel blends. Issue 41 (22nd June 2018) - Irshad, Muhammad; Mujahid, Adnan; Afzal, Adeel; Bajwa, Sadia Z.; Hussain, Tajamal; Zaman, Waheed-uz-; Latif, Usman; Athar, Muhammad Makshoof
Abstract : A schematic representation of the developed setup for ethanol sensing measurements in gasohol blends. Abstract : Gasoline–ethanol (gasohol) fuel blends have gained considerable attention in the petroleum and energy sectors as relatively cheaper and greener high-octane alternative fuels with gasoline-comparable efficiency in modern transportation vehicles. However, due to different combustion rates the relative concentration of ethanol in gasohol fuel blends may vary over time. Furthermore, there is a need to monitor ethanol concentration in fuel blends for quality control applications. This article reports a miniaturized electronic sensor based on an interdigital capacitor (IDC) as the transducer and a dual-imprinted titania–polyaniline composite film as the receptor. The device has an active surface area of 0.9 cm 2 and is easy to fabricate. The receptor material is synthesized by imprinting ethanol in both titania sol (EITS, the matrix) and polyaniline nanoparticles (EIPani, the filler), and subsequently mixing them to obtain a dual-imprinted EITS–EIPani composite. The structural and morphological characteristics of the receptor layers are determined with Fourier transform infrared (FTIR) spectroscopy and atomic force microscopy (AFM), respectively. The IDC devices are fabricated with pristine EITS and dual-imprinted EITS–EIPani composite to test their metrological sensor characteristics in standard ethanol solutions and real-time gasohol fuel blends. The instant shift in capacitance is measured upon exposure to different concentrations of ethanol. These devices show excellent sensitivity and selectivity patterns and demonstrate reliable sensor response toward ethanol in different gasohol fuel blends with 1–10 vol% ethanol. The results of this study reveal that these miniaturized ethanol sensors are potentially useful for rapid analysis of ethanol in gasohol and may be optimized for onboard fuel quality control applications.